1963
DOI: 10.1111/j.1476-5381.1963.tb01501.x
|View full text |Cite
|
Sign up to set email alerts
|

The Increase in the Toxicity of Yohimbine Induced by Imipramine and Other Drugs in Mice

Abstract: In mice, yohimbine appears to accentuate the normal " alarm " reactions (alerting, flight) to external stimuli. Imipramine increases this effect and at the same time converts a non-lethal dose of yohimbine into a lethal one. The effect of imipramine is greatly reduced by adrenalectomy or by treatment with reserpine, syrosingopine, ganglion-blocking drugs or adrenaline antagonists acting on sympathetic 3-receptors. Hypnotic, anti-convulsant or anaesthetic agents, tetrabenazine or antagonists of 5-hydroxytryptam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

1965
1965
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 22 publications
1
27
0
Order By: Relevance
“…In contrast, Lacomblez et al [18] demonstrated an increase in plasma levels of clomipramine in patients receiving yohimbine which might be due to a decrease of hepatic clearance of yohimbine by clomipramine or more likely by demethylclomipramine. It has also been long known that yohimbine toxicity is potentiated by tricyclic antidepressants and phenothiazines [19].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Lacomblez et al [18] demonstrated an increase in plasma levels of clomipramine in patients receiving yohimbine which might be due to a decrease of hepatic clearance of yohimbine by clomipramine or more likely by demethylclomipramine. It has also been long known that yohimbine toxicity is potentiated by tricyclic antidepressants and phenothiazines [19].…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of these results, it may be deter mined that betamimetic drugs are capable of antagoniz ing reserpine hypothermia [Frances et al, 1978;Ross, 1980]. Malick [1981Malick [ , 1983 has shown that according to the technique of Quinton [1963] iprindole potentiates yo himbine toxicity. In the unanesthetized dog, it has been shown that iprindole potentiates the effect of yohimbine beginning at 9 mg/kg i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Beta-blockers reduce yohimbine toxicity [Quinton, 1963;Lapin, 1980;Bourin et al, 1988]. Propranolol, a central nonselective betai-and beta2-blocker [Giudicelli and Witchitz, 1983], metroprolol, a central selective betai-blocker [Witchitz, 1985], and atenolol, a nonselec tive betai-and beta2-blocker, not crossing the brainblood barrier [Berzin and Théry, 1981], were studied in the presence of iprindole 100 mg/kg in the yohimbine test: atenolol had no effect owing to its peripheral action, propranolol antagonized iprindole toxicity, whereas metoprolol had no effect.…”
Section: Discussionmentioning
confidence: 99%
“…The amphetamine induced hyperactiv ity in mice was antagonized by W2045, as it also is by reserpine (9). Yohimbine toxicity in mice is potentiated by amphetamine and it was considered by Quinton (19) that this was due to the increase in motility. In high doses W2045 produced ptosis in mice and in lower doses it potentiated reserpine-induced ptosis; similar potentiation is also claimed to occur with yohimbine (15).…”
Section: Discussionmentioning
confidence: 99%